Analysis of Macroeconomic Indicators (Case Study in North Sumatra Province) - Rahmadani Hasibuan; M. Ridwan; Yusrizal Yusrizal (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
The aim and direction of the research is to look at the causal or causal relationship between the independent (free) variables which consist of Economic Growth, Unemployment, and Inflation, and the dependent (bound) variable, namely poverty. The type of data used in this study is secondary data (Time Series The secondary data used in this study comes from various related agencies such as the Publication of the Central Statistics Agency which is accessed through the official website, as well as government agencies that can support this research data. Data collection techniques use a field research approach by collecting data from the variables Economic Growth, Unemployment, Inflation, as well as poverty obtained in processed form sourced from the Central Bureau of Statistics (BPS) of North Sumatra Province. In the t-test results, the variable Economic Growth on Poverty has a probability of 0.0387 < 0.05, so it can be said that the variable Economic Growth (x1) has a (significant) influence on poverty. The unemployment variable on poverty has a probability of 0.0248 <0.05, so it can be said that the unemployment variable (x2) has a (significant) influence on poverty. Also, the t-test results for the inflation variable on poverty have a probability of 0.8839 > 0.05, so it can be said that the inflation variable (x3) has no effect (not significant) on poverty. Meanwhile, based on the output results processed using Eviews 10 software, the calculated F value is 91.27120 while the F table with a level of α = 5% is 2.37. Thus F count > F table (91.27120 > 2.37), then it can also be seen from the probability value of 0.000000 which is smaller than the significance level of 0.05. This shows that the variables of Economic Growth, Unemployment, and Inflation together the same (simultaneously) have a significant effect on poverty in North Sumatra.